High-risk HPV is not associated with epithelial ovarian cancer in a Caucasian population. Issue 1 (December 2016) - Ingerslev, Kasper; Hogdall, Estrid; Skovrider-Ruminski, Wojciech; Schnack, Tine; Karlsen, Mona; Nedergaard, Lotte; Hogdall, Claus; Blaakær, Jan
Abstract Background High-risk human papillomavirus (HPV) has been suspected to play a role in the carcinogenesis of epithelial ovarian cancer (EOC). However, results from previous studies are conflicting. In most of these studies, the number of tissue samples was small. The current study was therefore undertaken to examine the prevalence of high-risk HPV DNA in EOC in a large series of patients. Method Formalin-fixed, paraffin-imbedded tumor tissue samples from 198 cases consecutively included in the Danish Pelvic Mass Study were analyzed. The material included 163 serous adenocarcinomas, 15 endometrioid adenocarcinomas, 11 mucinous adenocarcinomas and nine clear-cell carcinomas. Genotyping for high-risk HPV DNA was performed by real-time Polymerase chain reaction (PCR) using an in-house TaqMan singleplex assay targeting the E6/E7 region of the HPV 16 and 18 genomes. Additionally, 20 random samples without HPV 16 and/or 18 infections were reanalyzed for HPV subtypes 31, 33, 35, 39, 45, 51 and 52. Results The quality criteria were fulfilled in 191 samples. HPV 18 DNA was detected in one sample only, while the rest tested negative. The subgroup analysis for seven additional high-risk HPV subtypes was also negative. Conclusions Only one in 191 samples was positive for HPV DNA. We therefore conclude that high risk HPV is unlikely to be associated with EOC in a Caucasian population. Future studies should focus on other microorganisms as possible etiological factors in EOC carcinogenesis.